Giant Cell Tumor of the Uterus: A Report of 3 Cases With a Spectrum of Morphologic Features. (July 2015) - Bennett, Jennifer A.; Sanada, Sakiko; Selig, Martin K.; Hariri, Lida P.; Nielsen, Gunnlaugur P.; Oliva, Esther
Abstract : Giant cell tumors, a well-recognized neoplasm of bone, can rarely be found in the uterus. Such tumors are characterized by a dual population of mononuclear and osteoclast-like giant cells that lack epithelial and specific mesenchymal differentiation. In this study, the clinicopathologic features of 3 giant cell tumors of the uterus were reviewed. Immunohistochemistry for CD68, CD163, h-caldesmon, desmin, SMA, AE1/AE3, CD10, ER, PR, cyclin D1, CD1a, CD34, CD30, S100, myogenin/myoglobin, and Ki-67 was performed in all tumors, along with ultrastructural analysis in one. The patients were 47, 57, and 59 yr and the tumors measured 2.5, 7.5, and 16.0 cm. One neoplasm was confined to the endometrium, whereas the other 2 were myometrial. All 3 tumors showed a nodular growth comprised of mononuclear and osteoclast-like giant cells. The endometrial-confined tumor consisted of histologically benign mononuclear cells, whereas the others exhibited marked atypia. Mitotic activity was up to 5/10 HPF in the benign tumor and up to 22/10 HPF in the malignant. No cytologic atypia or mitoses were observed in the giant cells. CD68 and CD10 were strongly and diffusely expressed in both components of 3 and 2 neoplasms, respectively. Cyclin D1 was focal in the mononuclear cells and focal to diffuse in the giant cells. CD163 was diffuse in the mononuclear cells, but absent to focal in the giant cells. Ultrastructural analysis lacked diagnostic features of epithelial or specific mesenchymal differentiation. Both malignant tumors demonstrated an aggressive behavior. In summary, although rare, giant cell tumor of the uterus should be included in the differential diagnosis of benign or malignant tumors containing osteoclast-like giant cells.